FREE-TO-PLAY MOBILE GAME BUSINESS MAPPING WITH BUSINESS MODEL CANVAS - Adriatama, Irshad; Wandebori, Harimukti (Journal of Business and Management, 2017)
Abstract. ‘Free-to-play’ games do not need any initial payment in order to play it, but they have an in-game feature which lets the player to buy contents within the game by using real money. Despite being ‘free-to-play’, many people had paid for the in-game contents. An approach using the business model canvas is used in order to give more detailed insight about the business as a whole. Through this paper, a brief description about the ‘free-to-play’ mobile game industry had been able to be described, followed by the viewpoints from the ‘free-to-play’ mobile game players and the developer’s side. The approach used on this paper is by using qualitative and quantitative approach, by doing interviews as well as distributing questionnaire. The method used to gain the data is by doing interview, questionnaire, and content analysis. The player profile in is summarized so that the developer can know more about the players who played their games. By the research result, it is found that most player play the game for the game’s own intrinsic appeal rather than other factors. They are seeing the game as an outlet of made for self-satisfaction.  Keywords: mobile game, free-to-play, business model canvas, insight, technology, smartphone